PERFIL DO DESEMPENHO NEUROPSICOMOTOR EM ESCOLARES DA REDE MUNICIPAL DE IJUÍ/RS, EM 1/2010 - Pretto, Luciana M.; Sacon, Alana B.; Bonamigo, Elenita C. B.; Winkelmann, Eliane R. (Salão do Conhecimento, 2013)
Resumo